Axial behavior of full‐scale sandwich columns with different compressive strengths. (20th October 2020) - Choi, Seung‐Ho; Hwang, Jin‐Ha; Han, Sun‐Jin; Heo, Inwook; Lee, Doo‐Hee; Kim, Kang Su
Abstract: In this study, a total of six full‐scale sandwich columns were fabricated, and experiments on their load transfer performance were conducted. The effects of steel fiber reinforcement and the ratio of the column width to the slab thickness on the effective compressive strength were theoretically analyzed, and briefly compared the test results of full‐ and reduced‐scale specimens. The current design codes do not take into account the ratio of the column width to the slab thickness when estimating the effective compressive strengths of slabs and columns with different compressive strengths. The test results conducted in this study, however, showed that the effective compressive strength tended to decrease with increasing slab thickness. In addition, the specimen reinforced with steel fibers in the column region exhibited a higher effective compressive strength than the specimen with steel fibers in the slab region.